2020
DOI: 10.17759/cpp.2020280202
|View full text |Cite
|
Sign up to set email alerts
|

Professional Burnout, Symptoms of Emotional Disorders and Distress among Healthcare Professionals during the COVID-19 Epidemic

Abstract: The article presents the results of a synthesis by Australian and Canadian scientists (Kisely et al, 2020) of 59 reliable studies of the effects of work during various epidemics, including COVID-19, on mental health and well-being of medical workers in different countries. The research includes the level of professional burnout, symptoms of emotional ill-being, and distress data based on the analysis of a data sample from 248 involved healthcare professionals of Russian medical institutions. They anony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 5 publications
0
7
0
3
Order By: Relevance
“…We also collected information on age, gender, occupation and the duration of work with patients diagnosed with COVID-19. The total score of anxiety using GAD-7 was interpreted as: normal (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21) anxiety [23]. The cut-off score for the Russian version of SAVE-9 was taken as 18 [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also collected information on age, gender, occupation and the duration of work with patients diagnosed with COVID-19. The total score of anxiety using GAD-7 was interpreted as: normal (0-4), mild (5)(6)(7)(8)(9), moderate (10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21) anxiety [23]. The cut-off score for the Russian version of SAVE-9 was taken as 18 [24].…”
Section: Methodsmentioning
confidence: 99%
“…We also measured symptoms of depression using Patient Health Questionnaire (PHQ-9) [25]. The total score of depression was interpreted as: minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), severe (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) [25]. We used single items measures of emotional burnout and depersonalization derived from Maslach Burnout Inventory (MBI) scale to assess burnout [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Russian scientists also studied the psychoemotional characteristics of healthcare workers during the COVID-19 pandemic. It was shown that, at this time, a significant portion of healthcare workers experience severe symptoms of professional burnout and depression and have an increased level of anxiety and suicidal tendencies (Petrikov et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ограниченные ресурсы, продолжительные рабочие смены, нарушения сна и баланса между работой и личной жизнью, а также профессиональные риски, связанные с постоянным контактом с пациентами с COVID-19, способствовали дестабилизации психоэмоционального состояния у персонала МО. Среди факторов риска нарушений психического здоровья медицинских работников наиболее значимыми разные авторы считали: экстремальный характер ситуации, существенные изменения в профессиональной деятельности и образе жизни в целом [15], специфику течения COVID-19 (быстрое прогрессирование инфекции, тяжелые осложнения, недостаточные знания о новом заболевании) [16], высокую нагрузку на работе, снижение продолжительности и качества сна [17], возможность заразиться при оказании помощи пациентам [18], риск заразить членов своей семьи, близких [19], опасения, касающиеся недостаточного обеспечения средствами индивидуальной защиты (СИЗ) и расходными материалами [20], физический дискомфорт, связанный с необходимостью постоянного использования СИЗ [21], изолированность и чувство неопределенности ситуации [16,22].…”
Section: по итогам проведенного исследования получены актуальные данн...unclassified